Azerbaijan : Public Expenditure Review - World Bank (World Bank, Washington, DC, 2013)
Azerbaijan has experienced robust economic growth during the past seven years, aided by its oil sector development. Nevertheless, poverty is still pervasive and social indicators have deteriorated. The oil and gas windfall will be of undoubted benefit to the country and its citizens if combined with a very careful macroeconomic policy and fiscal stance, as well as steadfast implementation of the structural reform program and poverty reduction strategy. The experience of other resource rich countries has often been disappointing and left large strata of the population in continued poverty. The main challenge for Azerbaijan is to design and implement a policy agenda that leads to poverty reduction and improves incomes as well as equity, while maintaining macroeconomic and financial stability. This Public Expenditure Review (PER) focuses on the public expenditure part of the overall policy agenda. Its main objective is to provide a framework for more efficient use of public resources and more effective poverty reduction efforts. This framework is designed to be consistent with the maintenance of overall macroeconomic stability and with sustainable economic growth in the non-oil sector. The macroeconomic achievements over the past five years have been encouraging. Continuing these achievements, however, may present a greater challenge to the authorities in the coming decade. The relatively speedy accumulation of fiscal revenues related to the oil and gas windfall will create heavy spending pressures. Using these funds unwisely or out of the context of a sound vision of the country's sustainable economic development path will create macroeconomic instabilities, inefficient and non-competitive non-oil activities, or both. The basic conclusion and simple recommendation of this PER is that Azerbaijan follow a fiscal strategy consistent with sustainable development of the non-oil sector, while over time mending institutional weaknesses and structural deficiencies, and investing in its people.